Comparing Globalizations Historical and World-Systems Approaches (World-Systems Evolution and Global Futures,, 2018)
This work explores essential debates on globalization and world-systems analysis. It begins with a review of theoretical insights from world-systems analysis and explains the evolution of its terminology. The book subsequently seeks to answer several important questions: When did globalization begin and what insights into contemporary globalization may be gained from older forms? How does globalization differ in different places, and how can different instances of globalization be compared? Who is affected by globalization, how are they affected, and how do these effects vary, if at all, over time and space? As world-systems analysis and studies of globalization require interdisciplinary expertise, the contributing authors draw on many fields, including anthropology, economics, geography, philosophy, political science, sociology, and world history. The book's overall goal is to facilitate the dialogue between approaches that, at times, seem to "talk at cross-purposes," and to extend an invitation to scholars from many different areas to explore globalization.